Wound healing angiogenesis: A perspective of nurse - Andriany, Alia; Tahir, Takdir; Sjattar, Elly Lilianty; Ake, Julianus; Nuru, Hasanuddin (Global Health Management Journal, 2019)
- Abstract is not required -